Child Health and Economic Crisis in Peru - Paxson, Christina; Schady, Norbert (Published by Oxford University Press on behalf of the World Bank, 2014)
The effect of macroeconomic crises on child health is a topic of great policy importance. This article analyzes the impact of a profound crisis in Peru on infant mortality. It finds an increase of about 2.5 percentage points in the infant mortality rate for children born during the crisis of the late 1980s, which implies that about 17,000 more children died than would have in the absence of the crisis. Accounting for the precise source of the increase in infant mortality is difficult, but it appears that the collapse in public and private expenditures on health played an important role.